Factors Associated With C5 Palsy Following Cervical Spine Surgery: A Systematic Review. Issue 8 (December 2019) - Jack, Andrew; Ramey, Wyatt L.; Dettori, Joseph R.; Tymchak, Zane A.; Oskouian, Rod J.; Hart, Robert A.; Chapman, Jens R.; Riew, Dan
Study Design: Systematic review. Objectives: C5 palsy (C5P) is a not uncommon and disabling postoperative complication with a reported incidence varying between 0% and 30%. Among others, one explanation for its occurrence includes foraminal nerve root tethering. Although different risk factors have been reported, controversy about its causation and prevention persists. Inconsistent study findings contribute to the persistent ambiguity leading to an assumption of a multifactorial nature of the underlying C5P pathophysiology. Here, we report the results of a systematic review on C5P with narrow inclusion criteria in the hope of elucidating risk factors for C5P due to a common pathophysiological mechanism. Methods: Electronic databases from inception to March 9, 2019 and references of articles were searched. Narrow inclusion criteria were applied to identify studies investigating demographic, clinical, surgical, and radiographic factors associated with postoperative C5P. Results: Sixteen studies were included after initial screening of 122 studies. Eighty-four risk factors were analyzed; 27 in ≥2 studies and 57 in single studies. The pooled prevalence of C5P was 6.0% (range: 4.2%-24.1%) with no consistent evidence that C5P was associated with demographic, clinical, or specific surgical factors. Of the radiographic factors assessed, specifically decreased foraminal diameter and preoperative cord rotation were identified as risk factors for C5P. Conclusion: Although risk factors for C5P have been reported, ambiguity remains due to potentially multifactorial pathophysiology and study heterogeneity. We found foraminal diameter and cord rotation to be associated with postoperative C5P occurrence in our meta-analysis. These findings support the notion that factors contributing to, and acting synergistically with foraminal stenosis increase the risk of postoperative C5P.